2014
DOI: 10.1007/s12028-014-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury Associated Coagulopathy

Abstract: Isolated severe TBI is not an independent risk factor for the development of coagulopathy. However, severe TBI patients who develop coagulopathy have extremely high mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 31 publications
2
61
0
1
Order By: Relevance
“…8 Prolonged prothrombin and partial thromboplastin times usually occurred late, indicating a transition from a hyper-to a hypocoagulable state. 8,9 Despite strong clinical and laboratory evidence of its presence and association with poor clinical outcomes, 12 the pathogenesis of TBI-associated coagulopathy remains poorly understood. Current clinical tests detect the coagulopathy, but are insufficient to determine its causes or to predict its occurrence, making clinical management of TBI-associated coagulopathy difficult and costly.…”
Section: Introductionmentioning
confidence: 99%
“…8 Prolonged prothrombin and partial thromboplastin times usually occurred late, indicating a transition from a hyper-to a hypocoagulable state. 8,9 Despite strong clinical and laboratory evidence of its presence and association with poor clinical outcomes, 12 the pathogenesis of TBI-associated coagulopathy remains poorly understood. Current clinical tests detect the coagulopathy, but are insufficient to determine its causes or to predict its occurrence, making clinical management of TBI-associated coagulopathy difficult and costly.…”
Section: Introductionmentioning
confidence: 99%
“…20 It seems that potassium plays a role in pathophysiology of brain injury.The relation between coagulopathy and TBI was evaluated in previous studies and they reported that coagulopathy can occur frequently in patients with poor outcome. 30,31 This study also showed higher mortality rate among patients presented with higher levels of PTT but no statistically significant relation between coagulation factors and long-term GOSE was observed.…”
Section: Discussionmentioning
confidence: 57%
“…63 Coagulopathy can occur in isolated head injury, and the development of coagulopathy after brain injury is associated with a worse outcome. 64 The release of tissue factor from injured cortical parenchyma may contribute to, or even be responsible for, the development of coagulopathy and, when severe, subsequent disseminated intravascular coagulation. 64 The release of cerebral gangliosides and plasminogen-rich substrates from damaged brain tissue is also thought to contribute to coagulopathy in patients with severe head injury.…”
Section: Hematologicmentioning
confidence: 99%
“…64 The release of tissue factor from injured cortical parenchyma may contribute to, or even be responsible for, the development of coagulopathy and, when severe, subsequent disseminated intravascular coagulation. 64 The release of cerebral gangliosides and plasminogen-rich substrates from damaged brain tissue is also thought to contribute to coagulopathy in patients with severe head injury. 65 On the other hand, in a recent prospective observational study of 345 patients with isolated severe traumatic brain injury, no association with the development of coagulopathy was found.…”
Section: Hematologicmentioning
confidence: 99%
See 1 more Smart Citation